PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBANTUAN EDPUZZLE PADA MATERI BANGUN RUANG DI MTS SULTAN HASANUDDIN - Nabila; Ermawati; Lisnasari Andi Mattoliang; Sri Sulasteri; Ahmad Farham Majid (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Mathematics learning on solid geometry is often considered difficult due to the limited media used, therefore more interactive media are needed. This study aimed to develop an interactive learning media assisted by Edpuzzle that is valid, practical, and effective. The type of research is Research and Development (R&D) using the 4D model (Define, Design, Develop, Disseminate). The research instruments included validation sheets, teacher and student response questionnaires, student activity observation sheets, learning implementation sheets, and learning achievement tests. The subjects were 23 seventh grade students of MTs Sultan Hasanuddin. The results showed that the developed media had a validity level of 95% (very valid). Practicality was indicated by teacher responses of 85% (very good) and the implementation of learning in the 'implemented' category. Effectiveness was shown by student activities of 90% (very active), student responses of 87.36% (very good), and 86.96% of students achieving the minimum mastery criteria with an N-Gain of 0.54 (moderate improvement). Therefore, the interactive learning media assisted by Edpuzzle was declared valid, practical, and effective to be used in mathematics learning on solid geometry.